-2(x+2)=4-(5x-7)

Simple and best practice solution for -2(x+2)=4-(5x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x+2)=4-(5x-7) equation:


Simplifying
-2(x + 2) = 4 + -1(5x + -7)

Reorder the terms:
-2(2 + x) = 4 + -1(5x + -7)
(2 * -2 + x * -2) = 4 + -1(5x + -7)
(-4 + -2x) = 4 + -1(5x + -7)

Reorder the terms:
-4 + -2x = 4 + -1(-7 + 5x)
-4 + -2x = 4 + (-7 * -1 + 5x * -1)
-4 + -2x = 4 + (7 + -5x)

Combine like terms: 4 + 7 = 11
-4 + -2x = 11 + -5x

Solving
-4 + -2x = 11 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-4 + -2x + 5x = 11 + -5x + 5x

Combine like terms: -2x + 5x = 3x
-4 + 3x = 11 + -5x + 5x

Combine like terms: -5x + 5x = 0
-4 + 3x = 11 + 0
-4 + 3x = 11

Add '4' to each side of the equation.
-4 + 4 + 3x = 11 + 4

Combine like terms: -4 + 4 = 0
0 + 3x = 11 + 4
3x = 11 + 4

Combine like terms: 11 + 4 = 15
3x = 15

Divide each side by '3'.
x = 5

Simplifying
x = 5

See similar equations:

| 4x+6=2+3x-1 | | (n-2)*3=4n-10 | | -5x-49=113 | | 3t-14=2t+10 | | 6.1=-9+x | | 8x*4+4=68 | | x=81/(9(10-1)) | | 2(x+2.50)=16.00 | | X-2=3.7 | | 6a-54=5a+25 | | 1+3n=8+2n | | 12x3/9y8= | | x=81/9(10-1) | | 7.0-3x=1 | | X*2+1=3x+11 | | 5(3x+6)+4=15x+34 | | 2/7x=56 | | 20a*48a= | | 4y+7=4y-6 | | c+19.1=12.1 | | 3(n+1)=6n-9 | | X+3=-2x+12 | | 20a+48a= | | L+21=(-l)+87 | | v/4--10=13 | | |cos(x-pi/4)|=rad2/2 | | 5m-4+3m=24 | | z/3=1.49 | | 8x=17x-3 | | 7w+4-2=6w+4 | | 13=2j+5 | | -3p+9=-6 |

Equations solver categories